Logistics performance measurement framework for companies with multiple roles. Issue 2 (15th July 2019) - Irfani, Dian Prama; Wibisono, Dermawan; Basri, Mursyid Hasan
Abstract : Purpose: Companies with multiple roles, as both a profit generator and public service provider, have specific characteristics that differentiate them from single-role companies. However, literature suggests that no performance measurement framework exists to fully suit the characteristics of such companies. This study aims to develop a novel performance-measuring framework to manage logistics performance in multiple-role companies. Design/methodology/approach: The framework is developed by combining a literature review and a case study approach as applied to a company with multiple roles. The case study is conducted to identify the characteristics of multiple-role companies, the factors that potentially affect such companies' logistics performance and criteria for a new framework. The literature review identifies the concepts, performance attributes and indicators from existing frameworks with the potential for incorporation and synthesis in the new framework. Findings: This study identified several characteristics, performance drivers and criteria for a logistics performance-measuring framework for multiple-role companies. Additionally, this study successfully developed a new logistics performance-measuring framework that consists of eight performance management stages and an aggregated index to measure overall logistics performance. Practical implications: The proposed logistics performance-measuring methodology provides useful guidance for stakeholders of multiple-role companies to plan, organize, execute and evaluate logistics performance. Originality/value: This research fills a theoretical gap by explaining the characteristics of logistics systems in multiple-role companies, as well as the factors that may affect such companies' logistics performance. Further, the proposed framework contributes to academia by integrating performance attributes from several available frameworks to manage objective conflicts, dynamism issues and the inconsistent performance evaluations that exist in companies with multiple roles.